CRITICAL HOLISM APPROACH IN EARLY CHILDHOOD EDUCATION: A METHODICAL DISCUSSION - Orozco Castro, Cynthia (2014)
This lecture results from an action research carried out in two kindergartens: “Centro Infantil Laboratorio” and “Centro Infantil Ermelinda Mora” during this year. These kindergartens base their curriculum on critical and holistic attention to children. Therefore, the objective was to decode and transform educative spaces from a dialogical and transformational perspective. Participants evaluated institutional holistic and critical proposals from the perspective of coherence between educational goals and daily activities, basing problem-solving on the implications of hidden curriculum in both, proposals and processes.